Jihad Pasca Resolusi Jihad dalam Konteks Indonesia: Studi Interpretasi Tafsir Tematik Kontekstual Relevansi - Abd. Muqit; Muhammad Al Faruq; Komaru Zaman; Andressa Muthi’ Latansa; Muhammad Fikri Alkhoir; Arina Tanjaliana (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
The rise of jihad terminology usage lately (such as Sosmed jihad, jihad defending religion, jihad against election fraud, jihad forming Islamic State up to jihad terrorism) in Khawatikan provoked and is misunderstood by Muslims, Given the real jihad (jihad against the suppression of Dutch colonizers, Lan'natullah) was completed after the resolution of jihad and Indonesian independence. Departing from the authors' research on jihad post-resolution jihad by tapers to the major orderly Islam, the Qur'an, and Hadith, by interdisciplinary thematic interpretation methods using related scholarly approaches. Results concluded that the resolution of the Jihad is a fatwa of scholars '-clerics ' deliberations that have two meanings substantials: First, recognizing the validity of the State of the Unity of the Republic of Indonesia; Second, obliging all Muslims to follow the Jihad against an allied Dutch British Army returning to Indonesia. While Jihad post-resolution jihad only covers jihad seeks and develops Islamic sciences, jihad improves the quality of the lust of amarah and lawwamah toward the lust that is in God, namely the lust Muthmainnah, Jihad against Sulthon the Dhalim using Constitutionally, and jihad against the hypocrisy of hoks and slander.